A Subarachnoid Hemorrhage Presenting as Massive Nasopharyngeal Bleeding: A Case Report. Issue 1 (1st July 2018) - Zvara, Jessica; Hafen, Ryan D.; Angelotti, Timothy
Abstract : Patients who present with a subarachnoid hemorrhage may have more than 1 intracranial aneurysm at risk, which may not be appreciated until a subsequent aneurysmal bleeding event occurs. We describe a patient who underwent successful aneurysmal clipping, but later presented urgently with large-volume epistaxis 48 hours after the procedure. After successful intubation of the patient, subsequent angiographic imaging determined that the massive intranasal/oral hemorrhage was due to bleeding through the former operative site, from rupture of a previously unrecognized aneurysm. This series of events demonstrates the importance of selecting the most at-risk aneurysm for surgical intervention.